A study of awareness towards wasiat amongst Bank Rakyat customers / Raja Shurawardi Raja Nor Najiha - Raja Shurawardi, Raja Nor Najiha (Faculty of Business and Management, 2011)
This paper is aim to study the level of awareness among customer at Bank Rakyat Jerteh towards the concept of wasiat. The researcher will gather the data and information through questionnaire that are distributed to the customer of Bank Rakyat in order to measure their awareness towards wasiat concept and the importance of its in their life. There are some research result shows that wasiat is a practice that is being claim in Islam and it’s easy to perform by Muslim. However, the reality is the level of awareness among customer Bank Rakyat towards wasiat is still low even there is some of them already had an experience make wasiat. So, its importance for the people to get aware about wasiat early through education system in order to support the people nature towards wasiat practices for their benefit. At the same time they need to change their attitude towards wasiat and need to feel that wasiat is one of the important things in human life. However, in order people want to do that the responsible bodies such as Bank Rakyat and Amanah Raya Berhad or others need to conduct an effective promotion to the society regarding the wasiat.